2020
DOI: 10.1024/1662-9647/a000221
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Age and Pain With 9-Year Functional Health Trajectories

Abstract: Abstract. We investigated whether information-processing speed and accommodative coping moderate associations of age and pain with 9-year functional health trajectories. Our sample consisted of 5,254 participants of the German Ageing Survey aged 40 years and older ( M = 62.33 years) who participated in up to four measurement occasions. After controlling for sex, chronic diseases, and education, our longitudinal multilevel regression models revealed that the association of older age and higher pain severity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Besides the mechanism of pain serving as an “aging body reminder” and thereby affecting subjective age, it could also be that the detrimental effects of pain on quality of life and functional ability (Covinsky et al, 2009; Frede et al, 2023; Gerhardt et al, 2011; Jakobsson et al, 2003, 2004; Potter et al, 2022; Rudy et al, 2007; Wettstein et al, 2020; Willman et al, 2013; Zimmer & Rubin, 2020) result in an older subjective age. Indeed, increases in depressive symptoms were found to be related with increasing subjective ages over time (Ayalon et al, 2016), and an experimental study showed that inducing sad mood makes individuals feel older (Dutt & Wahl, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the mechanism of pain serving as an “aging body reminder” and thereby affecting subjective age, it could also be that the detrimental effects of pain on quality of life and functional ability (Covinsky et al, 2009; Frede et al, 2023; Gerhardt et al, 2011; Jakobsson et al, 2003, 2004; Potter et al, 2022; Rudy et al, 2007; Wettstein et al, 2020; Willman et al, 2013; Zimmer & Rubin, 2020) result in an older subjective age. Indeed, increases in depressive symptoms were found to be related with increasing subjective ages over time (Ayalon et al, 2016), and an experimental study showed that inducing sad mood makes individuals feel older (Dutt & Wahl, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Barrett and Gumber (2020) found that an increase in everyday body problems, including pain, prospectively predicted an older subjective age in a sample of older adults. Given that pain is a risk factor for poorer quality of life (Frede et al, 2023; Gerhardt et al, 2011; Jakobsson et al, 2003, 2004; Potter et al, 2022; Willman et al, 2013), restricted functional health (Covinsky et al, 2009; Rudy et al, 2007; Wettstein et al, 2020; Zimmer & Rubin, 2020) and greater mortality hazards (Tesarz et al, 2019; Zhu et al, 2007), it is possible that such associations are to some extent driven by subjective age.…”
Section: The Present Studymentioning
confidence: 99%
“…Next, they were presented with a list of digits and were asked to complete as many matching symbols as possible within 90 s. Our outcome was the number of correct responses. The test has been used in previous studies based on the DEAS (Seidler & Wolff, 2017; Wettstein et al, 2020; Zwar et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The detrimental consequences of pain for developmental outcomes such as quality of life and mental health (9)(10)(11), functional ability (12)(13)(14) or longevity (15,16) are wellestablished from prior research. Yet, little is known with regard to long-term trajectories of pain among the oldest-old as well as with regard to their predictors.…”
Section: Trajectories Of Pain In Very Old Age: the Role Of Eudaimonic...mentioning
confidence: 99%